2013
DOI: 10.1111/resp.12109
|View full text |Cite
|
Sign up to set email alerts
|

Severe vitamin D deficiency is associated with non‐tuberculous mycobacterial lung disease: A case‐control study

Abstract: Patients with NTM lung disease have a high prevalence of severe VDD and VDD was independently associated with NTM lung disease. Further studies are needed to examine causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
1
29
2
Order By: Relevance
“…Furthermore, the low incidence of NTM infections in warmer months could be linked to seasonal variations in vitamin D levels. Variations in vitamin D metabolism previously have been linked to NTM susceptibility (24,25). However, in our study, patients and healthy controls did not differ in sunlight exposure, and vitamin D supplementation in the first year of life occurred more often in the NTM-infected cohort than in controls.…”
Section: Discussioncontrasting
confidence: 65%
“…Furthermore, the low incidence of NTM infections in warmer months could be linked to seasonal variations in vitamin D levels. Variations in vitamin D metabolism previously have been linked to NTM susceptibility (24,25). However, in our study, patients and healthy controls did not differ in sunlight exposure, and vitamin D supplementation in the first year of life occurred more often in the NTM-infected cohort than in controls.…”
Section: Discussioncontrasting
confidence: 65%
“…Dendritic cells that present antigens to T cells are inhibited by 1,25-dihydroxyvitamin D in their differentiation and activation [19]. Based on this evidence, a large number of trials have examined the link between vitamin D and several infectious conditions such as acute viral respiratory tract infections, recurrent group A streptococcal tonsillopharyngitis, and tuberculosis [20,21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D supplements reduce the risk of acute respiratory infection [6, 7]. Many observational studies have shown that vitamin D status is inversely associated with the prevalence of common colds [810].…”
Section: Introductionmentioning
confidence: 99%